Energy, Exergy and Performance Analysis of Small-Scale Organic Rankine Cycle Systems for Electrical Power Generation Applicable in Rural Areas of Developing Countries - Suresh Baral; Dokyun Kim; Eunkoo Yun; Kyung Chun Kim (Energies, 2015)
This paper introduces the concept of installing a small-scale organic Rankine cycle system for the generation of electricity in remote areas of developing countries. The Organic Rankine Cycle Systems (ORC) system uses a commercial magnetically-coupled scroll expander, plate type heat exchangers and plunger type working fluid feed pump. The heat source for the ORC system can be solar energy. A series of laboratory tests were conducted to confirm the cycle efficiency and expander power output of the system. Using the actual system data, the exergy destruction on the system components and exergy efficiency were assessed. Furthermore, the results of the variations of system energy and exergy efficiencies with different operating parameters, such as the evaporating and condensing pressures, degree of superheating, dead state temperature, expander inlet temperature and pressure ratio were illustrated. The system exhibited acceptable operational characteristics with good performance under a wide range of conditions. A heat source temperature of 121 °C is expected to deliver a power output of approximately 1.4 kW. In addition, the system cost analysis and financing mechanisms for the installation of the ORC system were discussed.